2020
DOI: 10.3390/min11010042
|View full text |Cite
|
Sign up to set email alerts
|

Wild Plants for the Phytostabilization of Phosphate Mine Waste in Semi-Arid Environments: A Field Experiment

Abstract: The management of mine waste has become an urgent issue, especially in semi-arid environments. In this context, and with an aim to inhibit the oxidation of the sulfide tailings of the abandoned mine of Kettara in Morocco, a store-and-release (SR) cover made of phosphate mine waste (PW) was implemented. In order to guarantee its long-term performance, phytostabilization by local wild plant species is currently the most effective and sustainable solution. This study aimed to assess the growth performance and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…After two ve getation seasons, it was found that the rooting depth of Atriplex semibaccata, Vicia sativa, Launaea arborescens, Peganum harmala and Asparagus horridus contained essentially higher concentrations of As, Cd, Cu, Ni and Zn. From the evidence of the field studies and lab-scale tests, the listed plants were assumed suitable for phyto-stabilization of the whole surface area of tailings dumps [30].…”
Section: Review Of Global Trends In Meeting the Ecological Challenges...mentioning
confidence: 99%
“…After two ve getation seasons, it was found that the rooting depth of Atriplex semibaccata, Vicia sativa, Launaea arborescens, Peganum harmala and Asparagus horridus contained essentially higher concentrations of As, Cd, Cu, Ni and Zn. From the evidence of the field studies and lab-scale tests, the listed plants were assumed suitable for phyto-stabilization of the whole surface area of tailings dumps [30].…”
Section: Review Of Global Trends In Meeting the Ecological Challenges...mentioning
confidence: 99%
“…Morocco's mining heritage is very rich in phosphates; it has been reported that it contains three quarters of the world's reserves, which allows it to rise among the four main universal producers and exporters (Hakkou et al, 2008;Hakkou et al, 2009;El Berkaoui et al, 2021). Moreover, around ten other minerals (zinc, lead, anthracite, iron, copper, barite, antimony, fluorite, cobalt, silver, and manganese) are regularly produced, and make it possible to enrich this heritage (Mehahad and Bounar, 2020;Zine et al, 2020). In addition, clays from Morocco occupy a predominant place in all sedimentary rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Native flora is known to establish a self–sustaining vegetative cover on marginal land such as mine deposits and support the resilience and recovery of the historical ecosystem ( Prach et al 2013 ). According to Mukhopadhyay (2010) , Sheoran et al (2010) and Zine et al (2021a) , native plants are known for their fast growth, ability to easily establish themselves in stressed environments and high tolerance to harsh climatic conditions ( Zhang et al 2020 ). Using native plants to restore a landscape can help to reverse a species loss trend caused by harmful anthropogenic activities given that in the long run, these plant communities require little maintenance ( Minas 2015 ).…”
Section: Introductionmentioning
confidence: 99%